THE ROLE OF CULTURE AND LOCAL WISDOM IN WOMEN COM-MUNITY IN THE DIGITAL ERA - Mulyaningsih Mulyaningsih (Efisiensi : Kajian Ilmu Administrasi, 2020)
Abstract: Culture and local wisdom in women community in digital era. The purpose of this article is to find out how the role of culture and local wisdom towards the women's community. This article was written because the involvement of women is still considered lacking in the digital era and also offices. This is caused by lack of competence, time, and access to information and computer technology. The culture of sharing organizations, hich is based on local culture and local wisdom, is needed as a counterweight to the women's community in the digital era. This research used a policy research approach which is defined as a type of research that investigate fundamental social problems that occur in society. The COI (Community of Inquiry) formulation is used in this article to overcome social problems in the digital age. From the research results, COI formulation is well implemented to increase empowerment and the role of women in the digital era, including its role in offices and in the family. Abstract: Budaya dan Kearifan Lokal dalam Masyarakat Perempuan di Era Digital. Tujuan dari artikel ini adalah untuk mengetahui bagaimana peran dari budaya dan kearifan lokal terhadap  komunitas perempuan. Artikel ini ditulis karena keterlibatan perempuan dinilai masih kurang di era digital dan juga perkantoran. Hal ini disebabkan oleh kurangnya kompetensi, waktu, dan akses terhadap informasi serta teknologi komputer. Budaya organisasi berbagi yang disadarkan pada budaya lokal dan kearifan lokal dibutuhkan sebagai penyeimbang bagi komunitas perempuan di era digital. Penelitian ini menggunakan pendekatan penelitian kebijakan yang didefinisikan sebagai jenis penelitian yang berupaya menyelidiki masalah sosial mendasar yang terjadi di masyarakat.  Formulasi COI (Comunity of Enquiry) digunakan untuk mengatasi permasalahan sosial di era digital. Dari hasil penelitian, diketahui bahwa formulasi COI baik diimplementasikan untuk meningkatkan peran dan pemberdayaan perempuan di era digital, termasuk perannya di perkantoran dan di keluarga.